Analysis of the Effectiveness of the Indonesian Economic Heroes Program (PENA) - Karnadi, Karnadi; Widodo, Teguh (International Journal of Educational Dynamics, 2024)
The Nusantara Economic Hero Program (PENA) is an initiative that aims to develop and empower local micro-business actors in various economic sectors in Indonesia. Ministry of Social Republic Indonesia has generated this program. This paper seeks to analyze the program's effectiveness in reducing poverty by empowering the economic welfare of local communities and its contribution to graduating poverty relief In this analysis, this study uses qualitative and quantitative approaches to evaluate various aspects of the PENA Program. It will analyze data on business growth, increased income, job creation, and other socio-economic impacts generated by the economic heroes involved in this program. In addition, it will also discuss the factors that influence the success of this program, including the role of government, financial support, market access, training, and availability of supporting infrastructure. Through this analysis, it is hoped that a deeper understanding of the effectiveness of the PENA can be obtained as well as recommendations for future development and improvement.